Striving to Become a Better Teacher: Linking Teacher Emotions With Informal Teacher Learning Across the Teaching Career - Huang, Xianhan; Lee, John Chi-Kin; Frenzel, Anne Christiane (Frontiers in Psychology, 2020)
The importance of informal teacher learning (ITL) to teaching effectiveness and student achievement has been repeatedly demonstrated, but there is limited research into the personal antecedents of ITL. We analysed the relationships between teacher emotions and participation in five different kinds of ITL activities (learning through media, colleague interaction, stakeholder interaction, student interaction, and individual reflection) among 2,880 primary teachers (85.49% female) with a large range of teaching experience. Regression analysis and structural equation modelling revealed a positive association between enjoyment and engagement in all five ITL activities. Anxiety was found to be negatively related to colleague interaction and self-reflection, and anger was found to be negatively associated with student interaction. Furthermore, anxiety and anger were negatively related to teaching experience, whereas enjoyment was independent from teaching experience. Most ITL activities were positively related to teaching experience, except for stakeholder interaction. Implications for teacher training and intervention programmes for in-service teachers are discussed.